Food pre-ordering system with customer feedback using android (FoPOS) / Mohamad Yusri Awang - Awang, Mohamad Yusri (Universiti Teknologi MARA, Shah Alam, 2015)
An increasing number of people are using smaii phones and the availability of good Internet communication has greatly changing the way people access and interact in implementing business applications. However, only several restaurants in this country still used traditional way in doing ordering the food. This will lead problems to customer service such as misunderstanding between customer and waiter during food ordering process. Besides that, the other flaw is requiring many employers especially waiters to serve many customers at the same time. Usually, this happen during peak hours because many customers will have their breakfast and dinner on this time. Therefore, this paper is about Food Pre Ordering System with Customer Feedback using Android (FoPOS) which is developed to overcome the current problem of food ordering system. The customers can make their food pre order using the smart phone in any place with the internet connection. The customers just nee d to fill in the application form about their information, food and also the time of they will an·ive to the restaurant for having their meals. The or dered make by the customer then will be sent to the database of the restaurant. The waiters in the restaurant will print out or write the ordered to be passed to the kitchen. Based on the finding and analysis, 23 respondents had answer ed the questionnaire and testing the FoPOS application on their mobile phone. After that, the researcher had analyzed and found out that the respondents are agreed with the system is attractiveness, the interface is user friendly and easy to use. Besides, respondents believe that FoPOS application can assist them in make the food ordering process become effectively.